Factors Influencing Gold Purchasing in Indonesia: A Literature Review - Fanny Rahma Wiranti; Wirda Nursanti (Jurnal Multidisiplin Indonesia, 2025)
This study aims to analyze the factors influencing gold purchasing and investment in Indonesia based on existing literature. Using the VOSviewer application, the study maps the relationships between keywords frequently appearing in studies related to gold purchasing, which are divided into two main clusters: global external factors and local Indonesian factors. The analyzed studies indicate that factors such as gold prices, promotions, investment literacy, and the socio-economic impact post-COVID-19 pandemic play a significant role in influencing consumer decisions to invest in gold. Additionally, gender factors in small-scale gold trade were also found to affect the dynamics of the gold market in Indonesia. This study provides insights into the complexity of factors influencing the gold market and offers recommendations for stakeholders to formulate policies and strategies that are more responsive to social and economic changes.